Efektivitas Pendampingan Hukum Oleh Advokat Terhadap Pemenuhan Hak-Hak Tersangka Dalam Proses Pemeriksaan Perkara Pidana - Syafri Mulyadi; Bima, Muh. Rinaldy; Arsyad, Nasrullah (Universitas Pahlawan Tuanku Tambusai, 2025)
The advocacy profession is known as a noble profession (officium nobile). Advocates are considered noble because they dedicate themselves and their obligations to the interests of society, not solely to their own interests. Legal counsel, often referred to as advocates, are part of the four pillars of law enforcement and must cooperate with other law enforcement officials police, prosecutors, and judges to achieve justice for society. Article 1, paragraph 1, of Law Number 18 of 2003 concerning Advocates states that an advocate is a person who professionally provides legal assistance, both inside and outside the court, fulfilling the requirements stipulated by this Law. Legal counsel holds a crucial position in the criminal justice system. This research aims to determine the effectiveness of advocates in fulfilling the rights of suspects. In practice, the rights of suspects are often disregarded during criminal investigations, particularly at the investigative stage. This discrepancy between the legal mandate (Das Sein) and the reality on the ground (Das Sollen) is a matter of serious concern and requires in-depth analysis to understand the challenges and formulate effective solutions to prevent such practices from recurring in future criminal investigations. Keywords: Advocate, Legal Counsel, Suspect, Investigation, Criminal Case.